In vitro studies to characterise different physico-chemical properties of some feed grains and their impact in monogastric nutrition. Issue 1 (1st January 2021) - Abd El-Wahab, Amr; Grone, Richard; Wilke, Volker; Ahmed, Marwa F. E.; Chuppava, Bussarakam; Visscher, Christian; Kamphues, Josef
Abstract: Characterisation of the variations in physico-chemical properties of grains may help to improve the feeding value of grains for animal nutrition. Thus, this study aimed to obtain more extensive quantitative ideas concerning different physico-chemical properties of wheat, hybrid rye, and barley. The samples were ground in a hammer mill using screen size of 1, 3, and 6 mm, respectively. The cumulative mean particle distribution at >1.0 mm of the ground grains showed significant differences between wheat and hybrid rye (4.63 and 9.13%, respectively). At dry sieve analysis of 6 mm screen size, hybrid rye had significantly higher mean particle size distribution of >1.0 mm (26.8%) than for ground wheat and barley. Ground wheat using a 1 mm mesh sieve had the lowest water holding capacity and swelling capacity (1.89 g H2 O/g dry matter (DM); p  = .001 and 1.33 mL H2 O/g DM; p  = .021, respectively) compared to hybrid rye and barley. Ground hybrid rye using a 1 mm mesh sieve had the significantly highest extract viscosity (6.22 mPa s). Ground wheat had the lowest ( p  < .001) corrected sediment rate. In general, ground hybrid rye had always a higher feed particle size >1 mm regardless of the grinding size. Ground wheat had the lowest water holding capacity irrespective of the grinding mesh sieve. Finally, hybrid rye in general is characterised by high extract viscosity (6.22 mPa s at 1 mm grinding size), which decreased with coarser grinding (3.75 and 3.10 mPa s at 3 and 6 mm, respectively). Highlights: Particle size distribution is directly affected by the grinding process. Water holding capacity and swelling capacity are two complementary measurements. Extract viscosity seems to be affected by grinding; however, the sedimentation rate is influenced by the grain type.